2005
DOI: 10.1159/000083640
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Effects on Intracellular pH Changes and ROS Production in HEPG2 Cells: Role of p38 MAPK and Phospholipase D

Abstract: Aims: The present study was performed to evaluate Atrial Natriuretic Peptide (ANP) effects on intracellular pH, phospholipase D and ROS production and the possible relationship among them in HepG2 cells. Cancer extracellular microenvironment is more acidic than normal tissues and the activation of NHE-1, the only system able to regulate pHi homeostasis in this condition , can represent an important event in cell proliferation and malignant transformation. Methods: The ANP effects on pHi were evaluated by fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Therefore, ROS, cAMP, PKC and NHE may be involved in the processes of protein carbonylation and actin glutathionylation after exposure to Cd in haemocytes of mussels. This statement is in accordance with previously published studies, indicating that ROS production could be induced by a NHE-dependent pathway (Rothstein et al, 2002;Sand et al, 2003;Baldini et al, 2005). However, further research is needed in order for this to be verified.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, ROS, cAMP, PKC and NHE may be involved in the processes of protein carbonylation and actin glutathionylation after exposure to Cd in haemocytes of mussels. This statement is in accordance with previously published studies, indicating that ROS production could be induced by a NHE-dependent pathway (Rothstein et al, 2002;Sand et al, 2003;Baldini et al, 2005). However, further research is needed in order for this to be verified.…”
Section: Discussionsupporting
confidence: 93%
“…4A). The production of reactive oxygen species (ROS) has been reported to increase when pHi was decreased, suggesting that ROS is also a major stress to cells under acidic environments (Baldini et al, 2005). Both the transcription and activity of MnSOD were significantly increased in siNone at pHe 6.3, while the suppression of MnSOD activity and significant cytoplasm acidification was observed in siCTIB at pHe 6.3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2005, Baldini and collaborators demonstrated that in HepG2 hepatoblastoma cells, ANP induced intracellular acidification by decreasing NHE-1 expression and activity [57]. These Authors suggested that the ANP effect on pH i was mediated by NPR-C receptors.…”
Section: Innovative Targets For Antitumor Activity Of Anpmentioning
confidence: 99%